Prolonged Hoarseness Caused by Arytenoid Dislocation After Anterior Cervical Corpectomy and Fusion. Issue 3 (February 2016) - Zhong, Zhuolin; Hu, Jianhua; Wu, Nan; Zhai, Jiliang; Qi, Fang; Weng, Xisheng; Jiang, Pengxiang; Cao, Jingchen; Zhang, Zhuhua
Abstract : Study Design: A case of arytenoid dislocation after anterior cervical corpectomy and fusion (ACCF) is reported. Objective: To emphasize that arytenoid dislocation could be a possible cause of prolonged hoarseness in patients after ACCF. Summary of Background: Prolonged hoarseness is a common postoperative complication of cervical surgeries, especially in the anterior approach. Postoperative hoarseness is usually associated with paresis of the recurrent laryngeal nerve (RLN). However, other causes such as arytenoids dislocation, which is often misdiagnosed as RLN palsy, should not be ignored either. Methods: We reported one case of arytenoid dislocation after ACCF and reviewed the related literatures. Results: One patient treated with ACCF experienced prolonged postoperative hoarseness. Arytenoid dislocation was confirmed by laryngoscopy examination and three-dimensional computed tomography (CT) scan. To deal with the problem, a closed reduction of cricoarytenoid joint was performed under general anesthesia. Fortunately, the motion of vocal fold became nearly back to normal after surgery and the patient recovered uneventfully. He was satisfied with the clinical outcome at the final follow-up. Conclusion: Arytenoid dislocation should never be ignored in the differential diagnosis of prolonged postoperative hoarseness after ACCF. This situation can be confirmed by CT scan, vocal cord electromyography (EMG), fiberoptic laryngoscopy, or strobovideolaryngoscopy. Once the diagnosis is established, appropriate treatment should be considered immediately. Level of Evidence: 3